Criza din teatrul României moderne – de la primul spectacol la criza actuală - Nițoi, Daniel (Calitatea Vieții, 2023)
Art played an important role in the development of world civilizations, being an integral part of the culture of every community. Its manifestation mirrors the structure of the psycho-social depths of the community from which it originates. That is why, in moments of crisis, art also expressed itself differently, depending on the position it takes in relation to the crisis. Romanian theatre is relatively young, but over time it has had quite a significant impact in world history, giving back to universal culture, remarkable actors and works of art that will remain benchmarks in world theatre and film for a long time. The article briefly analyzes the historical evolution of the theater in Romania, the major societal crises that crossed it, and the different ways in which it responded to the crisis, adapting or not to it. From the major historical crises in relation to the church, identity crises, or the crossing of the Two World Wars to the crisis of our times generated by Covid-19, the theatre had to resist and find resources in order no to lose its ability to manifest composing himself, willingly or not, in the social reality of which it was and is a part.